Role of semaphorin‐1a in the developing visual system of the disease vector mosquito Aedes aegypti. Issue 11 (31st July 2014) - Mysore, Keshava; Flannery, Ellen; Leming, Matthew T.; Tomchaney, Michael; Shi, Lucy; Sun, Longhua; O'Tousa, Joseph E.; Severson, David W.; Duman‐Scheel, Molly
<x xml:space="preserve">Abstract</x> Background: Despite the devastating impact of mosquito‐borne illnesses on human health, very little is known about mosquito developmental biology, including development of the mosquito visual system. Mosquitoes possess functional adult compound eyes as larvae, a trait that makes them an interesting model in which to study comparative developmental genetics. Here, we functionally characterize visual system development in the dengue and yellow fever vector mosquito Aedes aegypti, in which we use chitosan/siRNA nanoparticles to target the axon guidance gene semaphorin‐1a (sema1a). Results: Immunohistochemical analyses revealed the progression of visual sensory neuron targeting that results in generation of the retinotopic map in the mosquito optic lobe. Loss of sema1a function led to optic lobe phenotypes, including defective targeting of visual sensory neurons and failed formation of the retinotopic map. These sema1a knockdown phenotypes correlated with behavioral defects in larval photoavoidance. Conclusions: The results of this investigation indicate that Sema1a is required for optic lobe development in A. aegypti and highlight the behavioral importance of a functioning visual system in preadult mosquitoes. Developmental Dynamics 243:1457–1469, 2014. © 2014 Wiley Periodicals, Inc.